Understanding Individual Differences in Metacognitive Strategy Use, Task Demand, and Performance in Integrated L2 Speaking Assessment Tasks - Zhang, Weiwei; Zhao, Meijuan; Zhu, Ye (Frontiers in Psychology, 2022)
This study investigated the concept of individual differences (IDs) in the use of metacognitive strategies (planning, problem-solving, monitoring and evaluating), and its relationship with task demand and learner performance within Kormos’ (2006, 2011) Bilingual Speech Production Model from the lens of Chinese English-as-foreign-language learners (EFL) in the context of integrated L2 speaking assessment. To measure metacognitive strategies, we administered an inventory on 134 Chinese EFL learners after they completed a set of integrated L2 speaking assessment tasks. Descriptive analysis and a multiple linear regression were adopted for data analysis and results show that: (a) IDs displayed variance in Chinese EFL learners’ metacognitive strategy use. (b) Among the four metacognitive strategies under investigation, problem-solving was reported to be used the most frequently in a sharp contrast with monitoring, which had the lowest frequency. (c) Metacognitive strategies worked interactively, responding to task demands involved in the four integrated L2 speaking assessment tasks. (d) Chinese EFL learners’ use of metacognitive strategies, in individual and interactive working mode, had no relationships with their speaking performance. These results are expected to present some insights into the role of individual differences reflected by metacognitive strategy use during L2 speech production under assessment conditions, which will add robust evidence to the existing literature on L2 speaking, in particular on metacognitive strategy use in L2 speaking assessment. In the meanwhile, the findings will provide some empirical validation support for Kormos’ (2006, 2011) model, which will further provide some implications for L2 speaking instruction and assessment.